2004
DOI: 10.1017/s1357729800053972
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for resistance to nematode infections in Texel lambs and their utility in breeding programmes

Abstract: This paper addresses the inheritance of host resistance to gastro-intestinal nematode parasite infections in commercial Texel lambs, and the rôle of resistance to parasites in breeding programmes. In two flocks of Texel sheep, faecal egg counts following natural parasite challenge were measured on up to three occasions post weaning per lamb over a 4-year period, with 1385 and 287 lambs measured on the two farms. Live weight, and ultrasonically measured fat and muscle depth at weaning were available for each la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
48
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 24 publications
13
48
3
1
Order By: Relevance
“…Appropriately transformed FEC is a moderately heritable trait in lambs and responds to selection (Morris et al, 1997a(Morris et al, , 2000Bishop et al, 1996Bishop et al, , 2004Gruner et al, 2004). FEC tends to be less heritable in kids and does (Woolaston et al, 1992;Morris et al, 1997b;Mandonnet et al, 2001;Vagenas et al, 2002) but the last authors showed that responses to selection for decreased FEC can be achieved over a short time period.…”
Section: Parasitic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriately transformed FEC is a moderately heritable trait in lambs and responds to selection (Morris et al, 1997a(Morris et al, , 2000Bishop et al, 1996Bishop et al, , 2004Gruner et al, 2004). FEC tends to be less heritable in kids and does (Woolaston et al, 1992;Morris et al, 1997b;Mandonnet et al, 2001;Vagenas et al, 2002) but the last authors showed that responses to selection for decreased FEC can be achieved over a short time period.…”
Section: Parasitic Diseasesmentioning
confidence: 99%
“…Resistance to different species of nematodes tends to be related, with genetic correlations between the FEC values arising from different species or genera of parasites generally being close to 0.5 (e.g. Bishop et al, 2004) or higher in some cases (e.g. Gruner et al, 2004).…”
Section: Parasitic Diseasesmentioning
confidence: 99%
“…Genetic correlations between faecal egg counts and lamb growth are generally close to zero (Bishop et al, 2004;Khusro et al, 2004;Pollott and Greeff, 2004a,b), although some authors have reported strong, negative correlations (Bishop et al, 1996;Bouix et al, 1998) and others have noted unfavourable relationships, with growth rates positively correlated with faecal egg counts (Morris et al, 2000(Morris et al, , 2005. Published estimates of the genetic correlations between faecal egg counts and ultrasonic measures of muscle and fat depths are close to zero (Bishop et al, 2004;Pollott and Greeff, 2004a).…”
Section: Introductionmentioning
confidence: 97%
“…Although there is only limited evidence for differences in resistance among temperate breeds of sheep (Gruner et al, 1992;Eady et al, 1996;Fogarty et al, 2005), genetic variation has been found within breeds for resistance to a number of species of gastro-intestinal parasites for sheep maintained in a range of environmental conditions (see Bishop et al, 2004;Gruner et al, 2004a;Pollott and Greeff, 2004a;Pollott et al, 2004;Morris et al, 2005 for recent examples). Furthermore, selection experiments have achieved substantial gains (Woolaston and Windon, 2001;Morris et al, 2000Morris et al, , 2005 and farm scale trials (Gruner et al, 2002;Eady et al, 2003) have demonstrated both direct benefits of genetic improvement for the health of the individual and phenotypic benefits to the population through reduced pasture contamination (Bishop and Stear, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…counting the number of parasite eggs which appear in horse faeces. Also, the epidemiological features of horse infection suggest an overdispersion of faecal egg output, with 10-15% of horses excreting 80% of the eggs (Relf et al, 2013(Relf et al, , 2014 (Bishop et al, 2004;Kemper et al, 2011). In sheep, this genetic variability has been exploited for breeding purposes (Kemper et al, 2011;Sallé et al, 2012).…”
Section: Introductionmentioning
confidence: 99%